Identity construction and illness narratives in persons with disabilities - Glintborg, Chalotte; Mata, Manuel de la, 1961- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book investigates how being diagnosed with various disabilities impacts on identity. Once diagnosed with a disability, there is a risk that this label can become the primary status both for the person diagnosed as well as for their family. This reification of the diagnosis can be oppressive because it subjugates humanity in such a way that everything a person does can be interpreted as linked to their disability"--
OCLC-licensed vendor bibliographic record.
Keywords: People with disabilities -- Psychology; Identity (Psychology); Narrative inquiry (Research method); Disability studies; SOCIAL SCIENCE / Handicapped; SOCIAL SCIENCE / Sociology / General; MEDICAL / Research